Electronic commerce (e-commerce) adoption by small- and medium-sized enterprises in Terengganu : An empirical study of influencing factors / Muhammad Hamizan Hasan - Hasan, Muhammad Hamizan (Bachelor of Science (Hons.) Statistics, 2015)
Advances in technology and the internet worldwide nowadays have sparked a revolution of digital business concept known as e-commerce. The outbreaks of ecommerce arena produce a new concept of business operation and radically expected to be new phenomenon of economic development in developing countries. Intervention of the Small and Medium Enterprises (SMEs) in electronic commerce institutions make e-commerce more generally accepted and proving that the world currently is in a new era of electronic. Migrations of SMEs to use e-commerce applications become important agenda by the government due to the role of SMEs as the engine of the national economy and their contribution to the economic development of the country. Various benefits received by SMEs who had adopted ecommerce and this scenario should be the essence of their incentive to use more ICT. However, the facts have proved among previous research of e-commerce adoption by SMEs which particularly low in Malaysia. This scenario is due to the various obstacles which hamper SMEs to make transformation in their business. However, informative facts suggest that a variety of factors that can influence e-commerce adoption among SMEs. Thus, this research aims to identify the factors that influence SMEs to adopt e-commerce. With the use of a sample of 365 respondents or SMEs companies, a structured survey questions were distributed to the owners or top management of SMEs in Terengganu which involves three main areas such as Northern, South and Kuala Terengganu. This study tested four hypotheses related to the factors of e- commerce adoption and found that organizational readiness and external pressure was significantly has a positive relationship with e-commerce adoption. Meanwhile the factors of perceive ease of use and perceive usefulness relatively is not significant. In addition, the objective of the research to identify the SMEs in Terengganu whether adopt with e-commerce or not was fully achieved and found that there is low e-commerce adoption due to the SMEs are still familiar with basic applications. Hence, the results has lead to specific recommendations for SME owners to take the first step to be ready in terms of organizational readiness in their organization to adopt with e-commerce through accomplish their important source of adaptation such as financial, technology, values, culture, consistencies of work practices and locate skilled staff to ensure the use of e-commerce can effectively performed. In term of external pressure, SMEs was suggest to use e-commerce applications on a regular basis and take the initiative to use more advance ecommerce applications to enhance competitive advantages in the industry